Profiling bitter taste receptors (TAS2R) along the gastrointestinal tract and their influence on enterohormone secretion. Gender- and age-related effects in the colon - Jalševac, Florijan; Descamps-Solà, Maria; Grau-Bové, Carme; Segú, Helena; Auguet, Teresa; Avilés-Jurado, Francesc Xavier; Balaguer, Francesc; Jorba, Rosa; Beltrán-Debón, Raúl; Blay, Maria Teresa; Terra Barbadora, Ximena; Pinent, Montserrat; et al. (Frontiers in Endocrinology, 2024)
Extraoral bitter taste receptors offer intriguing potential for modulating metabolism and the gut-brain axis through dietary interventions. Our understanding of these receptors is limited, and data on their effects on ageing are scarce. The complexity conveyed by their high diversity, low expression levels and species-dependent variability challenges our comprehension. We used real-time PCR to examine the relative abundance of multiple TAS2R across different segments of gastrointestinal mucosa in four human cohorts and related them to enteroendocrine secretions at the colon site. TAS2R14 exhibited the highest expression levels in all analysed tissues. In contrast, TAS2R39, -38 and -42 consistently exhibited lower expression levels. Ageing was found to upregulate TAS2R4, -5, -13, -20 and GLP-1 mRNA in the descending colon. Stimulating TAS2R14 in Hutu-80 cells induced GLP-1 secretion, while stimulating TAS2R5 modulated GLP-1 and PYY secretion. Given the modifications TAS2R agonists may undergo along the GIT, as well as the distinctive expression patterns and possible functional roles of TAS2R receptors along the intestinal tract, our findings suggest the viability of a targeted strategy aimed at enhancing specific functions to improve health outcomes. This study offers valuable insights into the intricate interplay between bitter taste receptors, gut physiology and potential dietary interventions.